A desigualdade isoperimétrica - Silva, Charleson Clivandir de Araujo (2013)
In this work we treat the study the isoperimetric inequality, with primary focus in its demonstration, using geometry. It is divided in two parts. The preliminary chapter, which portrays some de nitions and propositions of the plane geometry regarding polygons, curves and relationships between area and perimeter, as well as a study on maximum, minimum, average and the principle of nite induction, that serve as basis for the next chapter. The second chapter, we have a little history of isoperimetric problem and demonstration of the isoperimetric inequality, initially for polygons and then the general case of a simple closed curve.